KENDALI MPC BERBASIS FILTER KALMAN UNTUK SISTEM EMPAT TANGKI - ULUM, ZAIFUL; AFFAF, MOH. (E-Jurnal Matematika; Vol 8 No 1 (2019), 2019)
A Four-tank system is a multi-input multi-output (MIMO) system consisting of four interconnected water tanks and two pumps. This paper deals with the control design of the four-tank system  using model predictive control (MPC) based filter Kalman. The objective of the control design is to regulate the output of the system towards the desired values. In this work, the optimal control to the system is determined  by means MPC controller where both output and input constraints to the system are explicitly considered. The filter Kalman is used to estimate the state of the system. Simulations by using Matlab are performed to verify the performance of the proposed control design. Simulation results show that the proposed control design can regulate the output of the system towards the desired values.